Molten pool behavior and its mechanism during selective laser melting of polyamide 6 powder: single track simulation and experiments. (14th June 2019) - Wu, Jinzhe; Zheng, Jinjin; Zhou, Hongjun; Yang, Runhuai
Abstract: The behavior of molten pool formed during selective laser melting is hard to evaluate due to the short interaction time, extremely small dimensions, and complex process. Especially for polymers, it is necessary to consider Marangoni flow and their viscoelastic characteristics when applied in numerical simulations. In this work, PA6 single tracks were simulated which contains these two features. We compared that the relationships between the Linear Energy Density (LED) and the behavior of molten pool, such as the temperature distribution, velocity field, geometry and stress field. The corresponding experiments, including the assessment of the depth of molten pool, and mechanical properties at different LED, were also conducted to contrast with simulation results. The results indicated that appropriate increase of LED gave rise to increased depth of molten pool and resulted in strengthened mechanical properties. When relatively high LED = 10 J m −1 was applied, the sintered parts had better properties were found.